Effects of Different Warm-Up Durations on Wingate Anaerobic Power and Capacity Results - Halit Harmancı; Mihri Barış Karavelioğlu; Aydın Şentürk; Arslan Kalkavan; Oğuzhan Yüksel (Sportif Bakış Spor ve Eğitim Bilimleri Dergisi, 2014)
The purpose of this study was to determine the effects of different warm-up durations (5, 10, 15, 20, 25, 30 minutes) on Wingate anaerobic power and capacity results. 13 male handball players volunteered to participate in this investigation. The anaerobic power and capacity values of the participants were determined by Wingate test. After a 5, 10, 15, 20, 25 and 30-minute warm-up efforts, participants were applied to anaerobic power and capacity tests performed at least within 48-hour intervals. Furthermore, after the study ended, participants were subjected to another second anaerobic test including 5-minute warm-up duration to determine whether this study created any training effects on the participants. At the end of One-way ANOVA test, it was found that there were no significant differences in terms of absolute peak power (F5,60=0.768; P>0.05), relative peak power (F5,60=0.908; P>0.05), absolute average power (F5,60=0.440; P>0.05) and relative average power (F5,60=0.347; P>0.05) of the handball players after the 5, 10, 15, 20, 25 and 30-minute warm-up durations. As a consequence of the performed study, Paired Samples T test was applied in repetitive measures to eliminate the possible training effects. The results indicated that there was no training effect in terms of absolute peak power, relative peak power, absolute average power and relative average power (p>0.05) At the end of this study, it has been found that different warm-up durations performed within 5 to 30-minute intervals on the bicycle ergometer at a certain intensity have no effects on the Wingate anaerobic power and capacity values.